Minding Your Business: How Entrepreneurs Manage Stress (Journal of Organizational Psychology, 2020)
In many aspects of our lives, there is as much stress with success as there is with failure. Successful entrepreneurs often achieve celebrity status in modern-day American culture. But many entrepreneurs have hidden secrets: before becoming a successful entrepreneur, they first struggled with periods of anxiety and despair. Since 1999, there has been a 30% increase in suicide in America and entrepreneurs are not immune to this alarming trend.In this paper, the authors examine how mindfulness can assist entrepreneurs with stress management, but also assist in opportunity recognition and management decision making.
Keywords: Organizational Psychology; Anxiety; Stress Management; Mindfulness; Entrepreneurs; Business